A Trusted Message Bus Built on Top of D-Bus - Will, Newton C.; Heinrich, Tiago; Viescinski, Amanda B.; Maziero, Carlos A. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2020: Anais do XX Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg.2020.19236, 2020)
A wide range of applications use Inter-Process Communication (IPC) mechanisms to communicate between each other or between their components running in different processes. A well-known IPC mechanism in UNIX-like systems is D-Bus, which allows processes to communicate by receiving and routing messages. Despite being widely used, such system lacks mechanisms to provide end-to-end data confidentiality. In this paper we propose the use of Intel Software Guard Extensions (SGX) to provide a trusted communication channel between local applications over the D-Bus message bus system. We obtained stronger security guarantees in message confidentiality and integrity while keeping a small Trusted Computing Base (TCB) and compatibility with the reference D-Bus system.